Gambaran Hasil Pemeriksaan HCV, HIV, dan VDRL Pada Pendonor Unit Donor Darah PMI Kabupaten Kudus - Lestari, Catur Retno; Saputro, Arief Adi (Indonesian Journal of Biomedical Science and Health; Vol 1 No 1 (2021): Agustus 2021DO - 10.31331/ijbsh.v1i1.1840, 2021)
Giving blood transfusions has a risk of transmitting infectious infectious diseases through blood transfusions, especially Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS), Hepatitis C, Hepatitis B, Syphilis, Malaria, Dengue Hemorrhagic Fever (DHF), as well as the risk of other transfusions that can threaten life. The risk of transmission of infectious diseases through blood transfusions depends on various things, including the prevalence of the disease in the community, the effectiveness of the screening used, the immune status of the recipient and the number of donors per unit of blood. The purpose of this study was to describe the description of the results of HCV, HIV and VDRL examinations on donors at the Indonesian Red Cross Blood Donor Unit, Kudus Regency during 2020. Donors at the Kudus Regency Blood Transfusion Unit during 2020. The study was carried out in February 2021 at the Unit Kudus District Blood Transfusion. Diagnostic tests are performed using the Frequency Distribution. The results showed that the number of reactive donors on HCV examination was 18 (0.11%), HIV was 9 (0.05%) and VDRL was 12 (0.07%) of the total 16,081 donors. Most of the reactive donors are male. This is because men are generally more active than women, while hepatitis is transmitted through bodily fluids, which may occur due to activity, for example, through wounds received at work or while shaving.